Kubernetes patterns reusable elements for designing cloud-native applications - Ibryam, Bilgin; Huss, Roland (O'Reilly Media, 2019)
"The way developers design, build, and run software has changed significantly with the evolution of microservices and containers. These modern architectures offer new distributed primitives that require a differnet set of practices than many developers, tech leads, and architects are accustomed to. This focused guide provides common, reusable patterns and principles for designing and implementing cloud-native applications on Kubernetes. Each pattern includes a description of the problem and a Kubernetes-specific solution. All patterns are backed by and demonstrated with concrete code examples. This book is ideal for developers and architects already familiar with basic Kubernetes concepts who want to learn how to solve common cloud native challenges with proven design patterns."--Provided by publisher